2004
DOI: 10.1085/jgp.200308986
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Ivermectin Facilitation of Human P2X4 Receptor Channels

Abstract: Ivermectin (IVM), a widely used antiparasitic agent in human and veterinary medicine, was recently shown to augment macroscopic currents through rat P2X4 receptor channels (Khakh, B.S., W.R. Proctor, T.V. Dunwiddie, C. Labarca, and H.A. Lester. 1999. J. Neurosci. 19:7289–7299.). In the present study, the effects of IVM on the human P2X4 (hP2X4) receptor channel stably transfected in HEK293 cells were investigated by recording membrane currents using the patch clamp technique. In whole-cell recordings, IVM (≤10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
218
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(250 citation statements)
references
References 37 publications
28
218
3
Order By: Relevance
“…The increase in current supports the idea that P2X 4 subunit is part of the receptor. Furthermore, the current decrease, which was not expected if only P2X 4 subunits were present, indicates that other subunits are involved in the receptor assembly [43]. Conversely, if P2X 4/7 heteromeric receptors were present, we should have observed an increase on the peak currents after 3 min of incubation with 3 μM ivermectin, a fact not seen in our results [4,19].…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The increase in current supports the idea that P2X 4 subunit is part of the receptor. Furthermore, the current decrease, which was not expected if only P2X 4 subunits were present, indicates that other subunits are involved in the receptor assembly [43]. Conversely, if P2X 4/7 heteromeric receptors were present, we should have observed an increase on the peak currents after 3 min of incubation with 3 μM ivermectin, a fact not seen in our results [4,19].…”
Section: Discussioncontrasting
confidence: 63%
“…The higher-affinity binding site (EC 50 =0.25 µM) is able to increase the maximal ATPactivated currents without changing the ATP concentrationresponse relationship. The action at the lower affinity binding site (EC 50 =2 µM) results in a slower deactivation rate and enhancement of the ATP affinity [43]. Moreover, ivermectin does not act on P2X 2 , P2X 3 , P2X 2/3 , and P2X 7 receptors but does so on heteromeric channels containing the P2X 4 subunit [25,4,19].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the selective positive modulator of P2X 4 receptors, ivermectin (Khakh et al, 1999a;Priel and Silberberg, 2004;Lalo et al, 2007) at 1-10 M, had no effect on ATP-induced currents in acutely isolated astrocytes (Fig. 6).…”
Section: Atp-induced Currentsmentioning
confidence: 92%
“…At present, the use of ivermectin seems to be the most appropriate tool to study P2X 4 receptor activation. Recently, single channel recordings of ATP-evoked currents through human P2X 4 expressed in HEK293 cells suggested that ivermectin increases maximal channel currents after binding to a high affinity site (pEC 50 =6.6) and may also bind to a low affinity site (pEC 50 =5.7) to increase the affinity of ATP by stabilizing the open channel conformation [44]. As ivermectin induced an increase in the NAD + -induced rise in [Ca 2+ ] i , we assume that P2X 4 receptors are involved in the NAD + response.…”
Section: Engagement Of P2x 4 Receptorsmentioning
confidence: 99%